SPECTRUM OCCUPANCY MEASUREMENT AND ANALYSIS AT OSUN STATE UNIVERSITY CAMPUS, OSOGBO, NIGERIA - HAMMED OYEBAMIJI LASISI; BOLATITO FATIMAH ADERINKOLA; FUNMILOLA MARGARET ADEAGBO (Journal of Engineering Studies and Research)
The rapid growth of new wireless communication applications and services has increased the demand for effective radio spectrum usage. However, present spectrum allocation policy has left some bands unoccupied. Through spectrum measurement, unoccupied spectrum can be identified and reallocated to unlicensed users without interfering with licensed users. This paper presents spectrum occupancy measurement of UHF TV bands from 470 MHz – 870 MHz conducted at six different locations in Osun State University, main campus, Osogbo. The results revealed that the spectrum occupancy values for the locations considered are: 16.6%, 11.9%, 18.9%, 23.1%, 17.7% and 19.4% respectively for locations 1, 2, 3, 4, 5 and 6. Only 17.9% of the spectrum, on the average, is effectively utilized. This indicated that large portion of the spectrum is unoccupied, and cognitive radio, stands a good chance of being deployed in the examined bands.